IDENTIFIKASI MISKONSEPSI MAHASISWA PENDIDIKAN FISIKA PADA MATERI RANGKAIAN LISTRIK - Muhammad Asy’ari (Lensa: Jurnal Kependidikan Fisika, 2016)
Misconceptions are concepts that are inconsistent with the scientific or scientific understanding received by scientists in the field concerned. This study aims to identify student misconception on dynamic electrical material. This study is a preliminary study in which, students' answers are analyzed based on the average Certainty of Response Index (CRI) listed on the answer sheet. In general, students are still experiencing misconceptions on dynamic electrical materials identified using 10 problems, namely: 1) wrong choice 60.72%; 2) correct choice of wrong reasons 33.46%; 3) correct choice true reason 4.98%; and 4) empty answer 0.79%. Based on the result, it can be concluded that students generally are still experiencing misconceptions on dynamic electrical materials so that comprehensive improvement needs to be done to overcome the problem.